Reduction of the Working Force, Defined (Relations industrielles / Industrial Relations, 1961)
SummaryA reduction of the working force means a reduction in any part of the working force, and is not to be limited to a reduction of the total number of employees.Shawinigan Chemicals Limited and Le Syndicat des travailleurs en produits chimiques de Shawinigan, Montreal, January 16, 1961, pp. 1-23. H. D. Woods Arbitrator.